Real-time rowing simulator with multimodal feedback - von Zitzewitz, J.; Wolf, P.; Novakovi, V.; Wellner, M.; Rauter, G.; Brunschweiler, A.; Riener, R. (Sports Technology, 2008)
Efficient rowing requires both physical and technical abilities of the human. Teaching and learning of the technical abilities is thereby mainly restricted to on-water training. The aim of this project was to develop a rowing simulator. This simulator should serve as a high-level indoor training tool that can be used by rowing novices and professionals. The users should perceive acoustic, visual, and haptic cues about their current performance and their environment in real time. The newly-developed rowing simulator consists of a rowing boat hull equipped with multiple position sensors attached to the oar and seat. The boat hull was mounted on a podium placed inside a Cave setup. The Cave comprises projection screens, a loudspeaker system, and actuated winches for visual, acoustic, and haptic feedback, respectively. A mathematical real-time rowing model was developed, which computes the boat velocity and the oar force as a function of the movement of the oar and the user. All relevant boat, oar, and user parameters can be arbitrarily set, thus allowing the simulation of different boat types. The rowing model was validated by comparing results of the simulation with data from on-water measurements. Both the boat velocity and the oar force predicted by the model correlated highly with the experimentally-obtained data. Furthermore, the rowing simulator was successfully tested with professional rowers who rated the level of realism and the applicability of the simulator for indoor training as high. Based on the feedback of the rowers, various hardware and software extensions are planned for the simulator, including an increase of the number of actuated degrees of freedom of the boat and the oar, in order to improve the haptic feedback.